Highly Accelerated Breath-Hold Noncontrast Electrocardiographically- and Pulse-Gated Balanced Steady-State Free Precession Magnetic Resonance Angiography of the Thoracic Aorta: Comparison With Electrocardiographically-Gated Computed Tomographic Angiography. Issue 2 (March 2019) - Lim, Ruth P.; Singh, Susan G.; Hornsey, Emma; Kearney, Leighton; Churilov, Leonid; Storey, Pippa; Begbie, Mark; Shoobridge, Jennifer; Xu, Jian; Rayner, Melanie; Matalanis, George; Smith, Gerard
Abstract : Objective: The aim of this study was to evaluate agreement of measured thoracic aortic caliber in patients with aortic disease, using electrocardiographically-(ECG) and pulse-gated breath-hold noncontrast balanced steady-state free precession MRA (ECG-MRA, P-MRA) at 1.5 T, compared with ECG-gated computed tomographic angiography (CTA). Methods: Thirty-one patients underwent ECG-MRA, P-MRA, and CTA. Two readers independently measured aortic caliber in 7 segments, with agreement between techniques and readers evaluated. Image quality was qualitatively assessed. Results: There was overall excellent agreement among ECG-MRA, P-MRA, and CTA for measured aortic caliber (Lin's concordance correlation coefficient ≥0.94, all comparisons); however, lower concordance was noted at the annulus (Lin's concordance correlation coefficient <0.6) at segmental assessment. There was excellent interreader agreement for aortic caliber for all 3 techniques (intraclass correlation coefficient >0.94). Image quality was poorer for both MRA techniques compared with CTA, particularly at the aortic root. Conclusions: Electrocardiographically-gated MRA and P-MRA at 1.5 T achieve comparable thoracic aortic measurements to gated CTA in clinical patients, despite inferior image quality.